Beneficiaries of A Place: Whose Life Is Better? - Rozhkov, Kirill L.; Khomutskii, Konstantin (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The paper shows relationships between the characteristics of residents and the places, where they live. A combination of three criteria of place attractiveness (retention and attraction, conditions for natural growth, and settling) was chosen to classify places, and profiles of their beneficiaries on the theoretical level. The results of the empirical study partially confirm the developed theoretical typologies. Two methods to segment place market are equal only if expectations of population are constant. Study results allow place marketers to identify emerging shifts in the structure of beneficiaries of specific places and predict their further evolution.